Relationship Analyst of Sort, Set in Order, Shine, Standardize, and Sustain (5s) Method With Quality Nursing Services - Fachruddin, Nanang; Purwaningsih, Purwaningsih; Krisnana, Ilya (Jurnal Ners, 2026)
The application of the sort, set in order, shine, standardise, and sustain (5S) method has the potential to improve the quality of nursing services by improving the efficiency and regularity of the work environment in hospitals. This study aimed to analyse the relationship between the 5S method and the quality of nursing services. This cross-sectional study included 50 patients selected using purposive sampling. Questionnaires on the application of the 5S method and quality of nursing services were administered, and relationship analysis was performed using Spearman’s correlation test. Correlation analysis showed a significant positive relationship with the strength of correlation between the application of the 5S method and the quality of protection services (r = 0.684; p = 0.045). The application of the 5S method contributes to improving the quality of nursing services by improving work efficiency, environmental orderliness, and patient safety. Therefore, the 5S method can be recommended as an effective quality management strategy for improving the quality of nursing services in hospitals.